The certified athletic trainer’s preparedness dealing with psychological issues of the collegiate student-athlete - Wieczorek, Mary H. (Kansas State University, 2012)
The purpose of this report is to review available literature that identifies various psychological issues collegiate student-athletes may face and how medical professionals, specifically certified athletic trainers (ATCs), are prepared to manage these psychological issues. Considering ATCs are in constant interaction with student-athletes in comparison to other medical professionals it is crucial that research is being completed to make sure athletic trainers are properly caring for student-athlete and acting quickly and appropriately to psychological issues. This report will review research on psychological aspects encountered by athletic trainers in contact with student-athletes, and; furthermore, the ATCs sense of comfort and competence in working with these issues. Questions may arise such as how well the ATC is able to assess the psychological issues and know when to assist or refer these matters, issues which may include training, competence, expectations, and ethical practice. Finally, the review of the research and literature in this area will lead to suggestions and implications for further research and continued understanding of the ATCs role in the psychological aspects of their work with student athletes.
Keywords: Collegiate student-athlete; Psychological issues; Athletic Trainer Certified (ATC); Certified athletic trainer; Clinical Psychology (0622)